2021
DOI: 10.3390/ijns7030047
|View full text |Cite
|
Sign up to set email alerts
|

Novel Modification of a Confirmatory SMA Sequencing Assay that Can Be Used to Determine SMN2 Copy Number

Abstract: Promising treatments for spinal muscular atrophy (SMA), the leading genetic cause of infant mortality, prompted calls for inclusion in newborn screening (NBS). In January 2018, the New England Newborn Screening Program (NENSP) began statewide screening for SMA using a tiered algorithm looking for the absence of SMN1 Exon 7. When results from the first and second tier needed reconciliation, we developed and validated a third tier DNA sequencing assay to ensure the presence or absence of SMN1 Exon 7. All nine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As an example, SMA analysis originally included a tiered algorithm looking for the absence of SMN1 Exon 7. When results from the first and second tier needed reconciliation, a third tier DNA sequencing assay was developed that confirms SMN2 copy numbers without the need for additional instrumentation [ 246 ]. A program report on screening 179,467 newborns confirmed the value of the screening algorithm in detecting SMA-affected infants who show absent SMN1 Exon 7 by Real-Time™ quantitative PCR (qPCR) [ 247 ].…”
Section: Resultsmentioning
confidence: 99%
“…As an example, SMA analysis originally included a tiered algorithm looking for the absence of SMN1 Exon 7. When results from the first and second tier needed reconciliation, a third tier DNA sequencing assay was developed that confirms SMN2 copy numbers without the need for additional instrumentation [ 246 ]. A program report on screening 179,467 newborns confirmed the value of the screening algorithm in detecting SMA-affected infants who show absent SMN1 Exon 7 by Real-Time™ quantitative PCR (qPCR) [ 247 ].…”
Section: Resultsmentioning
confidence: 99%
“…The review identified 37 cohort studies of newborn screening for SMA [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No RCTs of newborn screening were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Cohort studies relating to newborn screening programmes for SMA were identified from the following 17 countries ( Table 1 ): the UK [ 9 ], Belgium [ 10 , 11 , 12 ], Germany [ 13 , 14 , 15 , 16 , 17 , 18 ], Italy [ 19 , 20 ], Latvia [ 21 ], Portugal [ 22 ], Poland [ 23 ], Ukraine [ 24 ], Norway [ 25 ], Australia [ 26 , 27 , 28 , 29 ], the USA, Canada [ 30 , 31 , 32 ], Brazil [ 45 ], Japan [ 46 , 47 , 48 , 49 , 50 ], Taiwan [ 51 , 52 ], China [ 53 , 54 , 55 ] and Russia [ 56 , 57 ]. The USA screening programmes were reported for several US states: California [ 33 ], Georgia [ 34 ], Kentucky [ 35 ], Massachusetts [ 36 , 37 ], New York [ 38 , 39 , 40 ], North Carolina [ 41 ], Wisconsin [ 42 ], Utah [ 43 ] and Ohio [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MLPA test is performed by a different clinical laboratory, and it takes about 5 days to obtain the results (including the time required to transport the specimen). In addition to the MLPA method, measurement of the SMN2 copy number by droplet digital PCR [ 17 , 18 ] and real-time PCR [ 19 ] using DBSs has also been reported. Using these methods to measure the SMN2 copy number in the DBSs may shorten the time taken for diagnosis.…”
Section: Discussionmentioning
confidence: 99%